Keystone mutualism influences forest tree growth at a landscape scale. (26th July 2019) - Clark, Robert Emerson; Gutierrez Illan, Javier; Comerford, Mattheau S.; Singer, Michael S.
Abstract: Interactions between ants and phloem‐feeding herbivores are characterised as a keystone mutualism because they restructure arthropod communities and generate trophic cascades. Keystone interactions in terrestrial food webs are hypothesised to depend on herbivore community structure and bottom‐up effects on plant growth. Here, we tested this prediction at a landscape scale with a long‐term ant‐exclusion experiment on hickory saplings in the context of spatial variation in herbivore community structure and habitat quality. We quantified top‐down effects of ants, herbivore communities as well as abiotic factors impacting hickory shoot growth. We found that ants influenced shoot growth via strong, context‐dependent, compensatory effects, with clear cascading benefits only when phloem‐feeders were present and chewing herbivore abundance was high. By contrast, while several landscape variables predicted hickory growth, they did not mediate the strength of cascading effects of ants. These results suggest that ant/sap‐feeder mutualisms may regulate forest productivity by mediating effects of multiple herbivore guilds.